1991
DOI: 10.1088/0953-8984/3/38/008
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration in transition metals. II. Light interstitials in Cu, Ag, Ni, Pd, Al, V, Nb and Ta

Abstract: The electromigration wind valence of interstitial hydrogen in a series of transition metals is calculated using a state-of-the-art computational scheme accounting for the real band structure and local lattice deformation plus charge transfer in the impurity cluster. A microscopic picture of the oscillatory motion and the mobility of the proton explains the remarkable difference between the wind valence of hydrogen in Nb and Ta. A zero-point motion model explains the H/D isotope effect in the eiiective valence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Since no holes are present in a finite-cluster description of a solid, the Fermi surface, let alone details of it, is apparently not important, and the old naive picture broke down for electromigration in metals. However, such model results remain dependent on the cluster size to too great an extent [15], and the measured negative Z wind for hydrogen in tantalum could not be reproduced [14,16]. Therefore, embedding of the cluster in the complete host matrix remains important, as regards both the magnitude and the direction of the wind force.…”
Section: Theorymentioning
confidence: 98%
See 1 more Smart Citation
“…Since no holes are present in a finite-cluster description of a solid, the Fermi surface, let alone details of it, is apparently not important, and the old naive picture broke down for electromigration in metals. However, such model results remain dependent on the cluster size to too great an extent [15], and the measured negative Z wind for hydrogen in tantalum could not be reproduced [14,16]. Therefore, embedding of the cluster in the complete host matrix remains important, as regards both the magnitude and the direction of the wind force.…”
Section: Theorymentioning
confidence: 98%
“…The expressions to be calculated numerically have been derived in the framework of multiple-scattering theory. Within the muffin-tin approximation for the system potential, which has been shown to be a good approximation for electromigration of hydrogen in FCC and BCC metals [16], these expressions are exact. The individual atomic scatterers, the potentials of which are constructed from atomic charge densities calculated ab initio, enter the theory via their phase shifts at the Fermi energy.…”
Section: Theorymentioning
confidence: 99%
“…The work was inspired in part by the ingenious work of Coehn, which demonstrated that hydrogen absorbed into palladium migrated in an electric field in a direction consistent with the absorbed hydrogen carrying a positive charge (Coehn & Specht 1930)—interpreted as hydrogen being absorbed as interstitial atomic hydrogen that then dissociated to protons in the lattice. This phenomenon has subsequently turned out to be common in metals and has been much studied in recent years because of the importance of defect migration under high electric fields in interconnects in microelectronic circuits (Ho & Kwok 1989; Ek & Lodder 1991). Martin attempted the study of electrodiffusion in platinum.…”
Section: Student Days At Imperial Collegementioning
confidence: 99%
“…The growth of 〈111〉-oriented Cu interconnects is strongly desired in various fields such as in Si-LSI and 3D-LSI technologies, [1][2][3] because a Cu(111) plane with a densely packed face has high electromigration resistance. [4][5][6] In particular, the interconnect time delay and current density in Cu interconnects and through-silicon vias in 3D-LSI considerably increase with the shrinking of dimensions of LSI.…”
Section: Introductionmentioning
confidence: 99%